Strategi Dakwah Tokoh Agama Dalam Meminimalisasi Penyebaran Informasi Hoaks Di Desa Kasih Raja Kecamatan Lubuk Keliat Kabupaten Ogan Ilir - melsi Auliya (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to identify the da’wah strategies of religious leaders in minimizing the spread of hoax information in Kasih Raja Village, Lubuk Keliat Sub-district, Ogan Ilir Regency. The phenomenon of hoax dissemination in rural communities has become a serious issue, as it can influence social and religious conditions. The low level of digital literacy and the lack of public awareness in verifying information have contributed to the rapid spread of false news within the village environment. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The data sources consist of primary data obtained directly from religious leaders and community members, as well as secondary data derived from relevant literature and supporting documents. The results indicate that the types of hoaxes circulating in Kasih Raja Village are highly diverse, including fake news, misleading information, and provocative chain messages. Social media platforms such as WhatsApp and Facebook serve as the main channels for dissemination, with topics commonly related to social, political, health, and religious issues. To address this issue, religious leaders apply educational and persuasive da’wah strategies, including da’wah bil lisan through sermons and religious talks emphasizing the importance of tabayyun (verification) before sharing information; da’wah bil hal by setting a good example in using social media wisely; and da’wah bil hikmah by delivering religious messages politely and in accordance with the community’s social context. The supporting factors for the success of these strategies include the strong trust of the community toward religious leaders, the support of village authorities, and the enthusiasm of the community in participating in religious activities. Meanwhile, the inhibiting factors consist of low digital literacy, varied levels of education, lack of awareness of the negative impacts of hoaxes, and the strong influence of social media. Therefore, structured and continuous da’wah strategies play an essential role in fostering critical awareness and ethical media behavior within the rural community.